2015
DOI: 10.1016/j.amc.2015.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Parameter identification of BIPT system using chaotic-enhanced fruit fly optimization algorithm

Abstract: (2015) Parameter identification of BIPT system using chaotic-enhanced fruit fly optimization algorithm. Applied Mathematics and Computation, 268 . pp. 1267-1281 Bidirectional inductive power transfer (BIPT) system facilitates contactless power transfer between two sides and across an air-gap, through weak magnetic coupling. Typically, this system is nonlinear high order system which includes nonlinear switch components and resonant networks, developing of accurate model is a challenging task. In this paper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Parameter estimation plays an important role in bidirectional inductive power transfer (BIPT) systems. To obtain a proper parameter setting for this system, an improved algorithm using chaotic PSO to enhance the original FOA has been proposed [36], namely, CFOA, and the experimental results showed that the 11 parameters of this system were determined properly. In certain real-world problems, such as joint replenishment problems (JRPs), FOA has also been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Parameter estimation plays an important role in bidirectional inductive power transfer (BIPT) systems. To obtain a proper parameter setting for this system, an improved algorithm using chaotic PSO to enhance the original FOA has been proposed [36], namely, CFOA, and the experimental results showed that the 11 parameters of this system were determined properly. In certain real-world problems, such as joint replenishment problems (JRPs), FOA has also been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit fly optimization algorithm (FFOA) is a new swarm optimization algorithm which is inspired by the intrinsic behaviour of food search in fruit fly swarm [17][18][19][20]. The FFOA has been successfully adopted to deal with multi-objective optimization and scheduling problems.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the search efficiency and global search ability, researchers designed several improved FOAs [2].Yuan et.al [14] proposed a novel CFOA (chaoticenhanced fruit fly optimization algorithm), which employs chaotic sequence to enhance the global optimization capacity of original FOA. Wang et.al [15] introduced AM-FOA (adaptive mutation fruit fly optimization algorithm).…”
Section: Literature Reviewmentioning
confidence: 99%